Developing Students’ Worksheet based Educational Comic : Research and Development Study - Fajar, Arif; Smita, Marzia Khatan; Irhamudin, Irhamudin; Intamano, Banthita (CV. Creative Tugu Pena, 2022)
The article analyzed how the developing student worksheet based educational comic at sevent grade of SMP Taruna Jaya and to know the differences in student learning outcomes before and after the teacher used a student worksheet based educational comic at sevent grade of SMP Taruna Jaya. This research was conducted at seventh grade in first semester at SMP Taruna Jaya. This method used Research and Development (R&D). In this case, the research carried out only produces product designs, and the design is validated internally (experts and practitioners' opinions) but is not produced or not tested, external (field testing). The results of validation by a team of material expert validators, media experts and pre-test and post-test learners on products that are being developed have been declared valid. It was based on the results of validation of material experts and media experts by two lecturers and two teachers get a percentage of eligibility assessment of 90% with the criteria